Urgensi Kebijakan Digitalisasi Terjemah Kitab Suci Bahasa Daerah dalam Pelestarian Bahasa Daerah sebagai Warisan Budaya tak Benda - Zumara, Rita (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper discusses policies in the preservation of local languages in Indonesia from the threat of extinction due to various factors, such as migration, speaker attitudes, and the dominance of national and international languages because local languages have an important role in cultural identity and community knowledge systems. This paper aims to discuss the importance of policies that support the preservation of local languages through the potential application of digital technology while increasing people's religious understanding, using a qualitative method of policy review with a SWOT analysis approach, as well as a scoring-based evaluation. The results show that although the policy of digitizing translations of the Holy Scriptures can expand public access to regional language-based religious literacy, there are still some weaknesses that need to be overcome, namely (1) limited digital infrastructure in remote areas, (2) differences in the vision and priorities of various institutions in the collaboration process, (3) resistance from less prepared institutions, (4) maintaining the quality of digitization implementation and (5) sustainable funding. Therefore, this paper recommends several improvements, including:(1) Identification of local languages that require digitization and available resources. (2) Development of digital platforms, so that they are richer and more powerful. (3) Improve digital literacy by organizing training, socialization in local communities to facilitate technology adoption; (4) Integrate programs with national policies (5) Provide offline solutions to overcome internet network limitations.